Empowered communities tell their own stories from common bean production in Uganda - Akpo, E.; Ojiewo, Christopher Ochieng; Omoigui, L.O.; Rubyogo, Jean-Claude; Varshney, Rajeev K. (Springer, 2020)
Most smallholder farmers in Uganda often opt to farm the more popular crops which include coffee, plantain, cassava, sweet potatoes, and maize. Smallholder bean farming in Uganda is however overtaking the crops as farmers are seeing the potential that bean farming possesses. Women in the traditional Ugandan setting are considered as care givers and are tasked with ensuring food security. In Northern Uganda for instance, women are not entitled to inheriting land. When it comes to land sharing, women are only allowed to endorse the sharing. They are however given a portion where they can plant crops they can utilize in the household. The tropical legumes however strived to eradicate the stereotype that exists with the position of women in production for commercial purposes (Fig. 5.1).